Quality of life of patients with a colonic interposition postoesophagectomy. (12th December 2018) - Coevoet, Delfien; Van Daele, Elke; Willaert, Wouter; Huvenne, Wouter; Van de Putte, Dirk; Ceelen, Wim; Deron, Philippe; Pattyn, Piet; Van Nieuwenhove, Yves
Abstract: OBJECTIVES: After oesophagectomy, stomach grafts are most frequently used to restore intestinal continuity. Less frequently, a colonic graft is used. There is quite a large body of literature addressing the functional outcome after gastric pull-up, but little is known about the functional results of colonic interposition (CI). The aim of this study was to assess the short-term outcomes and the long-term quality of life and function of the CI postoesophagectomy. METHODS: Between 2002 and 2016, we retrospectively collected data on 80 patients with CI from personal health records at the Ghent University hospital. We prospectively compared the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30, EORTC QLQ-OG25 and Swallowing Quality of Life (SWAL-QOL) questionnaire scores to the healthy reference group and the gastric tube (GT) group. RESULTS: The 30-day mortality rate was 5%. Anastomotic leakage occurred in 37.5% and stenosis in 20% of the patients. The median overall survival of all patients was 33.9 months (95% confidence interval 8.3–59.4). The mean general health score of the CI patients was less than the healthy reference group but comparable to the GT group (CI = 62.1 vs healthy reference group = 71.2 vs GT = 60). Fifty percent of the patients reported their health as good and 15% as very good. The mean functional results with a CI were better than with a GT. Compared to GT patients, CI patients had less dyspnoea, reflux and dysphagia, but they reported more food selection, diarrhoea and weight loss. CONCLUSIONS: Despite the high complication rate, the severity of the disease and the demanding operation, patients perceived themselves as being in good health and reported very good long-term functionality after CI. Clinical trial registration number: B670201630635.